Metabolome Analysis of Banana (Musa acuminata) Treated With Chitosan Coating and Low Temperature Reveals Different Mechanisms Modulating Delayed Ripening - Parijadi, Anjaritha Aulia Rizky; Yamamoto, Kana; Ikram, Muhammad Maulana Malikul; Dwivany, Fenny M.; Wikantika, Ketut; Putri, Sastia Prama; Fukusaki, Eiichiro (Frontiers in Sustainable Food Systems, 2022)
Banana (Musa acuminata) is one of the most important crop plants consumed in many countries. However, the commercial value decreases during storage and transportation. To maintain fruit quality, postharvest technologies have been developed. Storage at low temperature is a common method to prolong the shelf life of food products, especially during transportation and distribution. Another emerging approach is the use of chitosan biopolymer as an edible coating, which can extend the shelf life of fruit by preventing moisture and aroma loss, and inhibiting oxygen penetration into the plant tissue. Gas chromatography-mass spectrometry metabolite profiling of the banana ripening process was performed to clarify the global metabolism changes in banana after chitosan coating or storage at low temperature. Both postharvest treatments were effective in delaying banana ripening. Interestingly, principal component analysis and orthogonal projection to latent structure regression analysis revealed significant differences of both treatments in the metabolite changes, indicating that the mechanism of prolonging the banana shelf life may be different. Chitosan (1.25% w/v) treatment stored for 11 days resulted in a distinct accumulation of 1-aminocyclopropane-1-carboxylic acid metabolite, an important precursor of ethylene that is responsible for the climacteric fruit ripening process. Low temperature (LT, 14 ± 1°C) treatment stored for 9 days resulted in higher levels of putrescine, a polyamine that responds to plant stress, at the end of ripening days. The findings clarify how chitosan delays fruit ripening and provides a deeper understanding of how storage at low temperature affects banana metabolism. The results may aid in more effective development of banana postharvest strategies.